AB0501 Sjögren Syndrome, Cancer Incidence and Mortality in Vigo Area. (15th July 2016) - Lorenzo, R.; Argibay, A.; Sousa, A.; Val, N.; Baroja, A.; Maure, B.; Freire, M.; Rivera, A.
Abstract : Background: Sjögren's syndrome (SS) is a systemic autoinflammatory disease with a well known epidemiological and laboratory characteristics. Its main symptoms are derived from exocrine glands affectation. Like other inflammatory diseases presents an increased incidence of malignancies. The diagnosis of this entity and subsequent identification of factors associated with the occurrence of tumors is important for early detection and management Objectives: To analyze the epidemiological, clinical and laboratory characteristics and the occurrence of lymphoma and mortality in a cohort of patients in a tertiary hospital diagnosed with SS Methods: Descriptive analysis of data collected retrospectively of patients with SS (criteria American-European 2002) between November 1989 and November 2012 the Hospital of Vigo Results: We describe 58 patients with SS of which 86% were women with a mean age of 53±15 years.Mean follow-up time was 69 months (range5–343). Mean age at diagnosis was 50 years (range 26–87 years).Only 6 (10%) had a secondary SS associated with Lupus Erythematosus Systemic, Rheumatoid Arthritis, Scleroderma, Mixed Connective Tissue Disease and Sarcoidosis. We do not find any autoimmune disease associated with organ-specific.The 84.5% and 93% had ocular and oral symptoms respectively.The parotid scintigraphy was performed in 25 (43%), which was pathological in 37 (68%).Salivary gland biopsy was performed in 30 (52%), 28 were diagnostic (93%).The most common extraglandular involvement was the joint (50%), followed the skin and lymph nodes (both 12%).24% have Raynaud's phenomenon with capilaroscopia nonspecific. Others, were central and peripheral nervous system (8.6% each one), respiratory (7%) and kidney (3%). None had muscle involvement. Anti-Ro was positive in 83% (59% also had anti-La) and anti-La was positive in only 48%.Antinuclear antibodies and rheumatoid factor were positive in 95% and 67% respectively. 22 (38%) had low C4 and 10 (17%) had low C3. Cryoglobulins were positive in 2 (3%). Only two patients have anti-Ro and anti-La negatives (they had xerostomia and xerophthalmia, parotid scan and biopsy compatible with the diagnosis). The cancer incidence was 10%, 2 were solid tumors (one pancreatic adenocarcinoma and another invasive ductal breast cancer) and 4 were hematologic (diffuse B lymphoma, angioimmunoblastic T lymphoma, Hodgkin's lymphoma and nodal MALT). All those who developed lymphoma they had previous lymphadenopathy. The mortality rate was 12%: 4 neoplasia (2 lymphomas, 1 pancreas and 1 breast), 2 infections, 1 cerebral hemorrhage. Conclusions: The 89.6% of our series had a primary SS with the same collected clinical and serological features literature. The development of a neoplasm was the leading cause of death (57.1%). In our cohort over half the patients who had lymphadenopathy developed a hematologic malignancy. SS patients have a higher risk for hematologic malignancy, so based on our data, the occurrence of lymphadenopathy it is a warning sign which requires us to actively seek a lymphoproliferative process References: Ramon-Casals et al. Guias de práctica clínica de la Sociedad Española de Medicina Interna. Diagnόstico Sjögren, 2009. Ramos-Casals M. et al. Prymary Syndrome Sjögren. BMJ, 2012 Turesson C et al. Malignancy as a Comorbidity in rheumatic diseases. Rheumatology, 2013 Disclosure of Interest: None declared